(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In the era of rapid industrialization, automation plays a vital role in enhancing efficiency and accuracy in manufacturing processes. This project presents the design and implementation of an Arduino-based color sorting system that automates the sorting of objects based on their colors. The system uses an infrared (IR) sensor to detect the presence of objects on a conveyor belt and a TCS3200 color sensor to identify their color. The Arduino microcontroller processes the sensor data and controls a servo motor that directs objects to designated bins according to their detected color red, green, or blue. This automated solution offers an affordable and effective alternative to expensive industrial sorting machines, making it suitable for small-scale industries and educational purposes. The system also addresses challenges such as sensor calibration and ambient light variations to ensure accurate color detection and sorting. Testing under various conditions demonstrates the system’s reliability, accuracy, and efficiency, highlighting its potential for wider adoption in automation and prototyping.